Robotic lateral transabdominal adrenalectomy. Issue 3 (15th July 2015) - Nomine‐Criqui, Claire; Brunaud, Laurent; Germain, Adeline; Klein, Marc; Cuny, Thomas; Ayav, Ahmet; Bresler, Laurent; Berber, Eren
<x xml:space="preserve">Abstract</x> Laparoscopic transabdominal adrenalectomy is considered to be the standard of care for adrnalectomy. Widespread adoption of robotic technology has positioned robotic adrenalectomy as an option in some medical centers. Many studies have compared laparoscopic versus robotic approaches to perform adrenalectomy and evaluated potential advantages to balance higher costs. This review summarizes current available data regarding the use of the robotic system to perform adrenalectomy (RA) and its comparison with laparoscopic adrenalectomy (LA). J. Surg. Oncol. 2015; 112:305–309. © 2015 Wiley Periodicals, Inc.